Complications in cesarean sections: A national survey of obstetric protocols and outcomes in Spain - María Jesús Cancelo Hidalgo; José Eliseo Blanco-Carnero; Lucas Cerrillos González (PLoS ONE, 2025)
Introduction Cesarean sections are among the most common obstetric surgeries worldwide. While generally safe, they can be complicated by numerous factors increasing risks for both mother and fetus, and posing significant challenges in clinical practice. In Spain, the absence of unified protocols for managing high-risk cases underscores the need for systematic guidance to improve maternal outcomes and reduce morbidity. Materials and methods A 45-question survey evaluated the management of complicated cesarean sections in Spain among members of the Perinatal Medicine Section of the Spanish Society of Gynecology and Obstetrics. The survey was developed and internally validated by the Spanish Society of Gynecology and Obstetrics. It was distributed online to all registered members. A total of 744 responses were collected between March and June 2024. Inclusion criteria were current obstetric practice and at least one year of experience. Results Data from 744 Spanish gynecologists was gathered. Respondents, had a median of 15.0 (P25-P75 = 17.0–24.0) years of experience, reported performing an average of 43.4 (SD = 62.1) cesarean sections per month, with 21.9% classified as complicated. Hospital level influenced case volume and complexity, with higher-level hospitals reporting higher incidence of complicated cesarean sections. Only 14.5% of institutions had established preoperative protocols for complicated cesarean sections, showing improved outcomes when implemented. Key complications included blood loss (1000–1500 ml in 35.3% of cases), fetal extraction difficulties, uterine atony, and adjacent organ trauma. Postoperative issues such as infections and wound dehiscence were also common. Conclusion This study highlights the need for standardized protocols in Spain to manage complicated cesarean sections. Their implementation could reduce intraoperative blood loss, decrease maternal morbidity from hemorrhage and trauma, and improve postoperative recovery and hospital stay duration.